Investigating Language Ego as an Affective Factor Influencing Second Language Acquisition in the Learning Process - Zahra, Dzahabiyah Alfiya; Nasrullah, Nasrullah; Rosalina, Elsa (Tell : Teaching of English Language and Literature Journal, 2023)
ABSTRACT: Real-life observation has shown that second language (L2) learners differ in their L2 learning process in which this individual difference is virtually related to the factors influencing second language acquisition. Many researchers have been interested in finding those factors, yet there is still a little study examining the impact of language ego as the affective factor. Thus, this paper aims to elaborate on how the language ego influences second language acquisition. By having a thorough understanding of language ego in L2 learning, it is expected that it can give some enlightenment to a better learning process for L2 learners.To provide an adequate explanation of language ego, this paper uses a literature review. This method is used to aggregate empirical findings related to a narrow research question which is the language ego as one of the affective factors influencing second language acquisition. Some previous studies that discuss a similar topic are collected, and the data is analyzed in accordance with the objective of this paper.As one of the affective factors, language ego is a psychological state of a learner in which it refers to the identity that a person develops in reference to the language. In this paper, it is hypothesized that the language ego influences second language acquisition in positive correlation when the focus is the permeability of the language ego. The permeability shows how the ego can be flexible and adaptable to the second language. The higher the learner’s language ego permeability is, the higher the learner’s chance of successful second language acquisition is.